Messengers of music : the legacy of Julia E. Crane - Collins, Caron L. (Emerald Publishing Limited : Information Age Publishing, 2011)
Music teachers around the world have positively influenced the lives of children. From Susan Udell who reaches out to over 3,000 students in Madison Wisconsin through her Hand-chimes program, to Deidre Roberts who shares the love of music to children in poverty stricken areas of Pakistan, Ecuador and Cambodia; many of these wonderful music teachers go unnoticed until now.This book is the result of research done by Dr. Caron L. Collins of the Crane School of Music at the State University of New York in Potsdam. Her research reveals the educational innovations and inspirational stories of nearly 50 music education alumni from over 2,000 graduates of the Crane School of Music, premier college of music education located in the North Country of New York State. These influential music teachers embody the ideals of Julia Ettie Crane, founder of this first institute for music educator training, nearly 125 years ago. The book gathers the stories of influential music teachers from the most notorious music schools in the United States, coupled with the life history of Julia Ettie Crane.Julia Ettie Crane was one of the important founders of our nation's music education over 100 years ago, but until now, no book has been written devoted to her contribution and her ongoing influence in today's classrooms. Thousands of music teachers have earned their degrees from her institute and have gone on to develop original music programs around the world. This book illuminates her forward-thinking philosophy from the archives of her personal writings and captures the selected stories gathered from many alumni to inspire current teachers to utilize these creative ideas in their school music programs. Public school music teachers will be encouraged and future music educators enlightened by the innovation of Miss Crane and her mission to educate all children through music.